2008
DOI: 10.1063/1.2957018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies of the flow over a circular cylinder at Reynolds number 3900

Abstract: This work contributes to the study of flow over a circular cylinder at Reynolds number Re= 3900. Although this classical flow is widely documented in the literature, especially for this precise Reynolds number that leads to a subcritical flow regime, there is no consensus about the turbulence statistics immediately just behind the obstacle. Here, the flow is investigated both numerically with large eddy simulation and experimentally with hot-wire anemometry and particle image velocimetry. The numerical simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

73
296
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(410 citation statements)
references
References 24 publications
(36 reference statements)
73
296
3
Order By: Relevance
“…Norberg 6 in his work, suggested that there is a change in the wake configuration at Re = 5000. This transition was later confirmed by Prasad and 12 Williamson, 41 while Norberg 39 attributed this change to a transition between a high-and low-quality vortex shedding mode. The results here presented suggest that at Re = 3900 both modes coexist and the wake is oscillating between them at a very low-frequency, and as has been shown this is the cause of the large scattering in the experimental and numerical results observed up until now.…”
Section: B Averaged Statistics In the Wakementioning
confidence: 66%
See 1 more Smart Citation
“…Norberg 6 in his work, suggested that there is a change in the wake configuration at Re = 5000. This transition was later confirmed by Prasad and 12 Williamson, 41 while Norberg 39 attributed this change to a transition between a high-and low-quality vortex shedding mode. The results here presented suggest that at Re = 3900 both modes coexist and the wake is oscillating between them at a very low-frequency, and as has been shown this is the cause of the large scattering in the experimental and numerical results observed up until now.…”
Section: B Averaged Statistics In the Wakementioning
confidence: 66%
“…For comparison, the solutions for each mode are plotted together with the experimental results from Parnaudeau et al 12 and the numerical results of Case I from Ma et al 11 (finer grid and larger span-wise domain). These reference solutions have been selected as both of them point out contradictory wake statistics due to their differences in the recirculation zone (L r /D = 1.51 and L r /D = 1.12, respectively).…”
Section: B Averaged Statistics In the Wakementioning
confidence: 99%
“…[8]. The modeling of the square plate is performed by an immersed boundary method, following a procedure proposed by [12]. Inflow and outflow boundary conditions are assumed in the streamwise direction, with a uniform fluid velocity U ∞ without turbulence as inflow condition and a 1D convection equation as outflow condition.…”
mentioning
confidence: 99%
“…Regarding the validation, studies as [4,5,6,7] using Incompact3d, presented both qualitatively and quantitatively results for conventional and complex flow geometries around fixed obstacles. According such studies, the code is a very attractive tool for solving flows in the context of Direct Numerical Simulations (DNS).…”
Section: Numerical Methodologymentioning
confidence: 99%
“…The principle of direct forcing is to preserve the no-slip boundary condition avoiding discontinuities in the first derivative at the cylinder surface [4].…”
Section: Numerical Methodologymentioning
confidence: 99%